Implementing Drilling Technique by Using Wondershare Quiz Creator to Improve Students’ Reading Ability - Muhammad Muchlisin (Jurnal Pendidikan Humaniora, 2014)
Abstract: This research was designed to improve the students’ reading ability through drilling tech-nique by using Wondershare Quiz Creator to solve the students’ problems. The design of this re-search was classroom action research and was conducted in 1 cycle which comprised four meetings. The stages in implementing this technique were (1) explaining about the topic through introduction page, (2) drilling the quiz based on the topic in every meeting then confirming the result, and (3) giving the final test in the last meeting. The results show that the implementation of this technique can improve the students’ reading ability. It can be identified that after the implementation of the ac-tion there was an improvement on the number of students  who got the score greater than or equal to 75. Key Words: reading ability, drilling technique, wondershare quiz creator Abstrak: Penelitian ini didesain untuk meningkatkan kemampuan membaca siswa melalui teknik drilling dengan menggunakan Wondershare Quiz Creator untuk mengatasi masalah siswa. Desain penelitian ini adalah penelitian tindakan kelas dan dilaksanakan dalam 1 siklus yang terbagi dalam empat pertemuan. Tahapan dalam penerapan teknik ini adalah (1) memberikan penjelasan mengenai topik pembelajaran melalui introduction page, (2) latihan kuis berdasar topik di setiap pertemuan ke-mudian mengkonfirmasi hasilnya, dan (3) memberikan tes akhir di akhir pertemuan. Hasil dari penelitian ini menunjukkan bahwa penerapan teknik ini dapat meningkatkan kemampuan membaca siswa. Dapat diketahui bahwa setelah menerapkan teknik ini ada perkembangan jumlah siswa yang mendapatkan nilai lebih besar atau sama dengan 75.Kata kunci: kemampuan bacaan, teknik drilling, wondershare quiz creator